Students’ Errors and Misconceptions about Operations of Fractions in an Indonesian Primary School - Ratnasari Ratnasari (SEAMEO Regional Centre for QITEP in Mathematics, 2018)
Fraction is one of the topics that is learned by students from primary, in secondary school and even college. When learning about fractions, sometimes students find difficulties that can trigger errors and misconceptions. This study was conducted to identify common students’ errors and misconceptions about operations of fractions (i.e. addition, subtraction, multiplication, and division) in an Indonesian primary school. The study used a qualitative methodology and involved 4 participants (S1, S2, S3, and S4) from 6th grade students from a classroom in a public primary school in South Jakarta. They were selected based on theirscores on a test on operations of fraction (15 problems). The four participants who were chosen, each got 2, 4, 6, and 14 answers correct. The result of this study indicated that for these four students, some errors about fractions in their primary school were errors in computing the fractions and mistyping the solutions. Some of the misconceptions of fractions were related to fraction operations.